Pengaruh Lingkungan Kerja, Beban Kerja, Disiplin Kerja Dan Motivasi Kerja Terhadap Kinerja Pegawai Pada Kantor Camat Tebing Tinggi Kabupaten Empat Lawang - Deri Saputra; Marko Ilpiyanto; Nisma Aprini (Jurnal Ekonomi Bisnis, Manajemen dan Akuntansi, 2024)
This study aims to determine and analyze the influence of the work environment, workload, work discipline and work motivation on employee performance at the Tebing Tinggi District Office, Empat Lawang Regency. The method used in this study is a quantitative method with several tests, namely validity and reliability tests, classical assumption tests and hypothesis tests (t-test, f-test, coefficient of determination). Based on the results of primary data regression processed using SPSS 24, the following multiple linear regression equations are obtained: Y = 7.411 + 0.239 X1+ 0.201 X2+ 0.266 X3+0.743 X4 + e. Partially, the Work Environment Variable ( X 1 ) has a positive and significant effect on Employee Performance due to the significance value of the variable X 1 0.009 which is less than 0.05 then H0 is rejected and H1 is accepted, The Workload variable ( X2 ) shows a positive and significant influence on Employee Performance. Because the significance value of the variable X2 is 0.016 which is smaller than 0.05, then H0 is rejected and H1 is accepted. The Work Discipline variable ( X3 ) has a positive and significant influence on Employee Performance, because the significance value of the variable X3 is 0.004 which is smaller than 0.05 , then H0 is rejected and H1 is accepted. The Work Motivation variable ( X4 ) has a positive and significant influence on Employee Performance, because the significance value of the variable X4 is 0.000 which is smaller than 0.05, then H0 is rejected and H1 is accepted. Simultaneously, the four Independent variables ( Work Environment, Workload, Work Discipline and Work Motivation ) together have a significant influence on Employee Performance with an F value of 22.632 and a significance of .000. The determination coefficient R2 of 0.673 or 67.3% states that the influence of the work environment (X1 ) , workload (X2) , work discipline (X3 ) and work motivation (X4 ) together on the employee performance variable (Y) is 67.3% while the remaining 32.7% is influenced by other variables not included in this study.